If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 225 = 10(x + -60) + 75 Reorder the terms: 225 = 10(-60 + x) + 75 225 = (-60 * 10 + x * 10) + 75 225 = (-600 + 10x) + 75 Reorder the terms: 225 = -600 + 75 + 10x Combine like terms: -600 + 75 = -525 225 = -525 + 10x Solving 225 = -525 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 225 + -10x = -525 + 10x + -10x Combine like terms: 10x + -10x = 0 225 + -10x = -525 + 0 225 + -10x = -525 Add '-225' to each side of the equation. 225 + -225 + -10x = -525 + -225 Combine like terms: 225 + -225 = 0 0 + -10x = -525 + -225 -10x = -525 + -225 Combine like terms: -525 + -225 = -750 -10x = -750 Divide each side by '-10'. x = 75 Simplifying x = 75
| 10x+21=15-21 | | (x^2)+(4x)+4=49 | | uy=-2/3x-2 | | 12x^2+7x+6=0 | | y=-30x+900 | | -8x^2-33+x^4=0 | | .52+.18s=3 | | 2x=6(x+5)-4 | | A/11=24/8 | | (y-3)/(y-2) | | 8(x+4)+7=10x-2(x-6) | | .52+.185=3 | | 6r-17=1+9r | | 5.32/1.4= | | y-3/y-2 | | (2x+6)+(3x+4)=90 | | -(x^2+x-2)= | | 8+4(4x-6)=5-4(2x+1) | | 5x^2-12x-65=0 | | 14*0.3= | | 2/3a^2b-1/6ab | | (2x-6)+(3x+4)=90 | | 4x^3+12x^2= | | y=(5x^2)-(2x)+3 | | 222+194+S=627 | | 32/2=×/1 | | 29+4y-2=15y-9-5y | | 13-2(x+51)=-19 | | 0.35(x+3)-.095(2x+28)= | | 222+194+5=627 | | (3x^2)-(5x)+1=0 | | 12x-7=0 |